2011
DOI: 10.3109/14767058.2011.589873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low versus high early parenteral nutrition on plasma amino acid profiles in very low birth-weight infants

Abstract: Although earlier more aggressive administration of AA and fat is not associated with any significant metabolic abnormalities, growth rates and plasma AA concentrations of the infants were similar to infants who AA and lipid given lower in the first day of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
3
30
0
4
Order By: Relevance
“…Previous studies reported that early PN was well tolerated and could be safely initiated immediately after birth, and that earlier more aggressive use of amino acid and fat was not associated with any significant metabolic abnormalities in preterm infants . The present findings support the safety of the early use of higher amounts of amino acid and lipid, and it was well tolerated without any adverse effect in preterm infants.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies reported that early PN was well tolerated and could be safely initiated immediately after birth, and that earlier more aggressive use of amino acid and fat was not associated with any significant metabolic abnormalities in preterm infants . The present findings support the safety of the early use of higher amounts of amino acid and lipid, and it was well tolerated without any adverse effect in preterm infants.…”
Section: Discussionsupporting
confidence: 86%
“…The present report confirms previous findings showing lower levels of arginine and citrulline in preterm neonates than in full‐term neonates . The low levels of arginine and citrulline in the premature neonates suggest that they are not capable of synthesizing the required amount of arginine.…”
Section: Discussionsupporting
confidence: 90%
“…Aggressive intakes of amino acids in the range of 2.5–3 g/kg/day starting on day one of life are well tolerated. [35,36]. The use of such aggressive nutrient intake is associated with increased protein accretion, decreased PNGR, better potassium homeostasis with decreased incidence of non-oliguric hyperkalemia, and decreased incidence of hyperglycemia by stimulation of endogenous insulin secretion.…”
Section: Early and Aggressive Nutritionmentioning
confidence: 99%